Adapting to Crisis: Accounting Information Systems during the Weimar Hyperinflation. Issue 3 (2020) - Hoffmann, Sebastian; Walker, Stephen P.
Abstract : German corporations are characterized as having been adaptable in the face of numerous traumatizing events during the twentieth century. This article explores how firms adapted their accounting information systems during the hyperinflation of the 1920s. It suggests that responses to the crisis focused on system elements identified as key to continuing operations. Initially, firms amended selling and purchasing arrangements, modified financial reporting, and shifted managerial reporting to nonmonetary information. As inflation accelerated, human resources were diverted to maintaining critical functions, especially those related to remunerating labor. While some elements of accounting systems fell into disrepair, there were also examples of innovation.